(untitled) (Fiep Bulletin - online, 2014)
This study aims to verify the hotel managers’ perception of the Physical Education professionals’ role in recreational programs offered by hotels in Gramado, Rio Grande do Sul. The descriptive study used semi-structured interviews with the managers of the hotels analyzed. The results show the physical structure, the recreational activities offered to the guests and the profile and training of the P.E. professional working in hotel recreational programs. It was found that the managers of the hotels analyzed are favorable to the work of the Physical Education professionals in the hotel market and that some of these hotels count on their participation in promoting the recreational programs.